Modulação vascular em rã touro, Lithobates catesbeianus - Duran, Lívia Maria (Universidade Federal de São Carlos, 2021)
Maintaining blood pressure stability is essential for cardiovascular homeostasis. Excessive fluctuations may cause deleterious problems such as vascular damage or reduction in tissue perfusion. Therefore, a series of mechanisms work on the fine adjustment of this variable, such as the baroreflex, which influences blood pressure through vascular adjustments and cardiac function alterations. The adrenergic and cholinergic systems likely modulate the vascular system. These mechanisms are poorly understood in amphibians, and they are potentially relevant since these animals are under the influence of gravity and are under potential hydric stress. Such factors can change vascular volume or affect hemodynamics with considerable effect on the cardiovascular system. Therefore, we evaluated the relevance of autonomic modulation of the vascular system in bullfrogs, Lithobates catesbeianus. The present work brings some new information about vascular modulation in this group. We observed that the adrenergic control has relative relevance for vascular adjustments. Despite being preponderant in the systemic circuit, adrenergic regulation is not the only responsible for MAP control. During hypovolemia, dual adrenergic blockade (inactivating vascular and cardiac sympathetic adjustments) did not affect the vascular parameters evaluated. Furthermore, we observed that cholinergic control is present and has higher relevance in the pulmonary vasculature.
Vascular modulation in bullfrog, Lithobates catesbeianus
Keywords: Modulação autonômica; Hipovolemia; Lithobates catesbeianus; Autonomic modulation; Hypovolemia; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA COMPARADA